Credit-Investment Space of Ukraine’s Regions and Institutional Mechanisms for Its Transformation in the Context of Economic Resilience - Khomyak, Myroslav; Shkurov, Yevhen; Bakalo, Ivan; Golovina, Olena; Bezzubko, Borys (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
This article examines the impact of the credit-investment space on regional economic resilience, taking into account the transformative role of institutional quality. The methodological framework is based on a phased approach that combines the development of integral indices and panel econometric modelling. The empirical analysis is based on regional data for 2020–2024. Aggregating indicators of lending, investment, and financial infrastructure constructed the credit-investment space index. The assessment was conducted using a panel model with regional and time fixed effects, supplemented by an analysis of marginal effects. The results confirm a statistically significant positive impact of financial space on economic resilience: a one-standard-unit increase in the index increases resilience by 17–21%, consistent with estimates from economies with transformational and peripheral regions. In the crisis year of 2022, the negative shock reduced economic stability by approximately 30%, but institutional factors partially offset this effect. The positive coefficient of interaction between financial space and institutional quality confirms the existence of a multiplicative stabilisation effect. The results obtained may be useful for the regions of Central and Eastern Europe, the Balkans and other economies facing asymmetric access to financial resources and increased crisis vulnerability.